Effect of thermal cycling and disinfection on colour stability of denture base acrylic resin - Goiato, Marcelo Coelho [UNESP]; Santos, Daniela Micheline dos [UNESP]; Baptista, Gabriella T.; Moreno, Amália; Andreotti, Agda M.; Bannwart, Lisiane C.; Dekon, Stefan F.C. (Wiley, 2012)
Objectives: The purpose of this study was to investigate the effect of thermal cycling and disinfection on the colour change of denture base acrylic resin. Materials and Methods: Four different brands of acrylic resins were evaluated (Onda Cryl, QC 20, Classico and Lucitone). All brands were divided into four groups (n=7) determined according to the disinfection procedure (microwave, Efferdent, 4% chlorhexidine or 1% hypochlorite). The treatments were conducted three times a week for 60days. All specimens were thermal cycled between 5 and 55°C with 30-s dwell times for 1000 cycles before and after disinfection. The specimens' colour was measured with a spectrophotometer using the CIE L*a*b* system. The evaluations were conducted at baseline (B), after first thermal cycling (T 1), after disinfection (D) and after second thermal cycling (T 2). Colour differences (ΔE) were calculated between T 1 and B (T 1B), D and B (DB), and T 2 and B (T 2B) time-points. Results: The samples submitted to disinfection by microwave and Efferdent exhibited the highest values of colour change. There were significant differences on colour change between the time-points, except for the Lucitone acrylic resin. Conclusions: The thermal cycling and disinfection procedures significantly affected the colour stability of the samples. However, all values obtained for the acrylic resins are within acceptable clinical parameters. © 2012 The Gerodontology Society and John Wiley & Sons A/S.
Keywords: Acrylic resins; Colour stability; Disinfection